Corporatism and the difusion of "organic representation" in european dictatorships - Pinto, António Costa (2016)
The paper examines the role of corporatism as a set of authoritarian institutions that spread across inter-war Europe and which was an agent for the institutional consolidation of fascistera dictatorships. Institutionalized, in many cases in the wake of polarized democratizations, inter-war dictatorships tended to choose corporatism both as a process for the repression and co-optation of the labour movement, interest groups and of elites through ‘organic’ legislatures. Powerful processes of institutional transfers were a hallmark of inter-war dictatorships and we argue corporatism was at the forefront of this process of cross-national diffusion of authoritarian institutions.